2005
DOI: 10.1007/s11103-005-3249-0
|View full text |Cite
|
Sign up to set email alerts
|

A reporter gene system used to study developmental expressionof alternative oxidase and isolate mitochondrial retrograde regulationmutants in Arabidopsis

Abstract: Perturbation of mitochondrial function causes altered nuclear gene expression in plants. To study this response, called mitochondrial retrograde regulation, and developmental gene expression, a transgenic Arabidopsis thaliana (Col-0) line containing a firefly luciferase gene controlled by a promoter region of the Arabidopsis alternative oxidase 1a gene (AtAOX1a) was created. The transgene and the endogenous gene were developmentally induced in young cotyledons to a level higher than in older cotyledons and lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 63 publications
2
65
0
Order By: Relevance
“…At least for the Arabidopsis AOX1a gene, induction is most likely the result of increased transcription controlled at a promoter region (Dojcinovic et al, 2005;Zarkovic et al, 2005).…”
Section: Mtros As Signals Affecting Nuclear Gene Expression and Cell mentioning
confidence: 99%
“…At least for the Arabidopsis AOX1a gene, induction is most likely the result of increased transcription controlled at a promoter region (Dojcinovic et al, 2005;Zarkovic et al, 2005).…”
Section: Mtros As Signals Affecting Nuclear Gene Expression and Cell mentioning
confidence: 99%
“…While a genetic system to elucidate these factors has been described (Zarkovic et al 2005), no factors using this system have been described as yet. Other approaches have identiWed the transcription factor ABI4 as a regulator of alternative oxidase ), where ABI4 acts as a repressor of alternative oxidase transcription, thus, upon stress treatment the alternative oxidase expression is repressed.…”
Section: Biogenesis: Transcriptional and Post-transcriptional Controlmentioning
confidence: 99%
“…Individual genes within the family are expressed differentially in response to a variety of stresses or developmental signals (reviewed in Vanlerberghe and McIntosh 1997;ArnholdtSchmitt et al 2006;Clifton et al 2006;Rhoads et al 2006;Rhoads and Subbaiah 2007). For at least some genes in some species, it has been shown that expression likely involves control at the level of transcription, although additional controls at the level of mRNA stability and translation may also exist (Yu et al 2001;Thirkettle-Watts et al 2003;Dojcinovic et al 2005;Zarkovic et al 2005). In T. brucei, the level of alternative 1 oxidase is controlled post-transcriptionally in a developmentally regulated fashion (Chaudhuri et al 2002).…”
mentioning
confidence: 99%
“…More broadly based mutant screens have been performed in Arabidopsis thaliana and Neurospora crassa. In A. thaliana, several genes were found that are required to induce the alternative oxidase, most likely at the level of transcription, in response to either antimycin A or monofluroacetate, an inhibitor of the Kreb's cycle (Zarkovic et al 2005). In N. crassa, alternative oxidase is encoded by the alternative oxidase (aod-1) gene.…”
mentioning
confidence: 99%